2022
DOI: 10.1097/md.0000000000028806
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Epstein-Barr virus-associated smooth muscle tumor with superimposed cryptococcal infection

Abstract: Rationale: Epstein-Barr virus-associated smooth muscle tumors (EBV-SMT) are rare, virally-induced malignancies that occur almost exclusively in immunocompromised individuals. We report a very rare case of a dura-based EBV-SMT with superimposed local cryptococcal infection.Patient concerns: An adult male with a history of untreated acquired immunodeficiency syndrome presented to our hospital with worsening headaches, diarrhea, and diffuse myalgias.Diagnoses: Blood cultures were positive for methicillin-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…A study by Deyrup et al examined EBV-SMTs in 19 patients with multiorgan involvement and found that, in each case, the tumors were genetically distinct, suggesting that the multiorgan condition arises from multiple primary tumors rather than metastasis [59]. Moreover, it has been observed that EBV-SMTs related to HIV infection tend to have a higher likelihood of central nervous system involvement [25][26][27]29,31,35,43,45,52,59].…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 99%
“…A study by Deyrup et al examined EBV-SMTs in 19 patients with multiorgan involvement and found that, in each case, the tumors were genetically distinct, suggesting that the multiorgan condition arises from multiple primary tumors rather than metastasis [59]. Moreover, it has been observed that EBV-SMTs related to HIV infection tend to have a higher likelihood of central nervous system involvement [25][26][27]29,31,35,43,45,52,59].…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 99%